A web-based, enterprise-wide, integrated information system as the source of high quality information for decision-making processes in the Department of Education in South Africa - Baxter, Claude Brian (Stellenbosch : Stellenbosch University, 2011)
Thesis (MPhil)--Stellenbosch University, 2004.